Human epidermal growth factor receptor-2 (HER2) is a potential therapeutic target in extramammary Paget's disease of the vulva. Issue 11 (November 2020) - Bartoletti, Michele; Mazzeo, Roberta; De Scordilli, Marco; Del Fabro, Anna; Vitale, Maria Grazia; Bortot, Lucia; Nicoloso, Milena Sabrina; Corsetti, Serena; Bonotto, Marta; Scalone, Simona; Giorda, Giorgio; Sorio, Roberto; et al.
Abstract : Background: Invasive vulvar Paget's disease with over-expression of the human epidermal growth factor receptor 2 (HER2) protein is potentially suitable for targeted therapy, especially in a metastatic setting where no effective treatments are available. Methods: Four consecutive patients with HER2 positive advanced vulvar Paget's disease, treated with weekly trastuzumab (loading dose 4 mg/kg, then 2 mg/kg) and paclitaxel (80 mg/m 2 ) followed by 3-weekly trastuzumab maintenance (6 mg/kg), are reported. Results: Median age and follow-up of patients were 62.5 years (45–74) and 16 months (6-54), respectively. Complete or partial responses were observed in all patients. Median time to response was 3 months (range 2–4), while median duration of response was 10 months (range 2–34). Case 1 presented with pulmonary and lymph nodes involvement. She experienced a radiological complete response after 24 treatment administrations, and a progression-free survival of 36 months. At disease progression, treatment re-challenge achieved partial response. She is currently receiving treatment with trastuzumab–emtansine. Case 2 was a 74-year-old woman who developed pulmonary metastasis after first-line cisplatin treatment. She had a partial response and a progression-free survival of 10 months. Case 3 had inguinal and para-aortic lymphadenopathy in complete response after 18 treatment administrations. She developed brain metastasis while receiving trastuzumab maintenance. Case 4 was treated for locally advanced disease and experienced a subjective benefit with relief in perineal pain and itching. No unexpected treatment-related side effects were reported. Conclusions: Advanced vulvar Paget's disease is a rare disorder and no standard treatment is available. In the sub-group of HER2 positive disease, weekly paclitaxel–trastuzumab appears to be active and safe, and may be considered a therapeutic option in these patients.